UPAYA MENINGKATKAN KEMAMPUAN SISWA DALAM MEMAHAMI PENJUMLAHAN DAN PENGURANGAN MELALUI PENGGUNAAN METODE BENDA KONKRET PADA SISWA KELAS IB SEMESTER II SD NEGERI BANDUNGREJO 1 2013/2014 - Sri Astuti (Universitas PGRI Semarang, 2014)
Mathematics as disciplines contributing to the development of the technology world has now reached the peak of sophistication in filling the needs of the various dimensions of human life. Evidence from the field suggests that the results of learning mathematics has always been at lower levels compared to other subjects. Facts on the ground indicate that the learning process is dilakukanoleh most teachers have only ranged delivery of content with lectures and notes. This resulted in the students quickly tired and bored with the learning of mathematics, especially for students in grade 1 primary school. To improve mathematics learning achievement in the subject matter of addition and subtraction of 2 digits, the authors use concrete objects learning media. Through the medium of this study are expected to mathematics learning achievement in the subject matter of addition and subtraction 2 numbers can be improved.This study uses a Class Action Research (PTK). The design of this research action research (Action Research) by using the spiral model. The stages in the implementation of this research is conducted through two cycles. In the classroom action research was used the analysis of quantitative data in the form of assessment of learning outcomes kognetif.Based on the results of research and discussion can be concluded that the concrete object learning media can enhance learning achievement of the addition and subtraction of two-digit numbers in Class IB Elementary School Bandungrejo 1 Semester 2 Karanganyar District of Demak second semester of the school year 2013/2014.?é?áKeywords: PTK, addition and subtraction, the method of concrete objects